Defoaming agent for garbage penetrating fluid treatment and preparation method thereof
By combining cellulose nanocrystals, hydrophobic modified graphene and other materials to construct a multi-level rough structure defoamer, the problems of poor effect and high cost in waste leachate treatment are solved, and high efficiency, economical and environmental protection are achieved The defoaming effect significantly improves the processing efficiency and environmental safety.
Patent Information
- Application Number
- CN202411433953.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-27
AI Technical Summary
In the treatment of existing waste leachate, chemical defoamers have problems such as poor defoaming effect, high cost, and short foam suppression time. Commonly used defoamers are prone to secondary pollution, making it difficult to completely eradicate foam, affecting the treatment efficiency and environment. Safety.
Cellulose nanocrystals and hydrophobically modified graphene are used as the framework materials to build a defoaming agent with a multi-stage rough structure by combining fluorosilicone copolymer, sorbitan liquid crystal, soybean lecithin and silica nanoparticles. Increase specific surface area and permeability, reduce surface tension, destroy foam structure, and improve stability and uniformity through optimized preparation process.
It achieves efficient, economical and environmentally friendly defoaming effects, significantly shortens the defoaming time and extends the foaming time, improves the processing efficiency and environmental safety, and is suitable for large-scale production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of defoamers, and in particular to a defoamer used for treating garbage leachate and a preparation method thereof. Background Art
[0002] With the rapid development of social economy and the continuous advancement of urbanization, the amount of urban domestic waste has shown an explosive growth trend. However, the construction of waste treatment facilities in my country is relatively backward, and most cities still mainly use traditional sanitary landfills to dispose of domestic waste. In the process of landfill, leachate is an inevitable by-product. Leachate refers to high-concentration organic wastewater that seeps out of the garbage layer during the stacking and landfilling of garbage due to the leaching and seepage of rainwater, surface water and the water contained in the garbage itself. It contains a large amount of organic matter, ammonia nitrogen, heavy metals and a variety of carcinogenic and teratogenic substances. It has the characteristics of high pollution load and complex and variable composition. If it is not handled properly, it is very easy to cause soil, surface water and groundwater pollution, endangering the ecological environment and human health.
[0003] The treatment of landfill leachate usually adopts biological method, physical and chemical method and membrane separation method, among which aeration biological treatment technology is widely used due to its high removal efficiency and low operating cost. However, the aeration process will produce a large amount of foam, which covers the liquid surface, hinders the transfer and dissolution of oxygen into the liquid, and reduces the aeration efficiency and treatment effect. At the same time, pathogenic microorganisms entrained in the foam are very likely to cause air pollution and infectious diseases during the dispersion process. Therefore, eliminating foam in the leachate treatment process is very important to ensure treatment efficiency and environmental safety.
[0004] At present, the commonly used defoaming methods in landfill leachate treatment are mainly physical defoaming and chemical defoaming. Physical defoaming destroys foam by mechanical impact, high-pressure spraying and other methods, which has high energy consumption, poor effect, and it is difficult to completely eradicate foam. Chemical defoaming is to add defoaming agents such as surfactants to reduce the surface tension of the liquid and destroy the foam structure, thereby achieving the purpose of defoaming. Compared with physical defoaming, chemical defoaming agents have the advantages of easy addition, quick effect, and thorough treatment, and have been increasingly widely used in the field of landfill leachate treatment.
[0005] Common chemical defoamers mainly include mineral oils, silicone oils, polyethers, fatty acid esters, etc. Among them, mineral oil defoamers have poor defoaming effect, large dosage, and are prone to secondary pollution; silicone oil defoamers have good performance, but are expensive, increasing operating costs; polyether defoamers have poor foam suppression effect and are prone to foam rebound; fatty acid ester defoamers are easily degraded by microorganisms and have a short foam suppression time. Therefore, the development of a new type of efficient, economical, and environmentally friendly defoamer has become an urgent need in the field of landfill leachate treatment.
[0006] In recent years, the development of bionics has provided new ideas and methods for the development of new functional materials. By learning from the excellent structure and function of natural organisms, bionic materials with unique properties can be designed. In the field of defoaming, research on bionic defoaming materials with natural hydrophobic structures has also begun, and they have initially shown good potential. However, most of these materials have problems such as complex preparation process, high cost, and poor stability, which limits their large-scale application.
[0007] The present invention is the result of our long-term research, and its conception comes from the hydrophobic self-cleaning characteristics of lotus leaves. Since the surface of lotus leaves has a multi-level rough structure composed of wax and nano-microstructures, it has super-hydrophobicity, and water droplets can roll freely on its surface and take away surface pollutants. According to this bionic principle, we use cellulose nanocrystals and hydrophobically modified graphene as skeleton materials, and by compounding functional components such as fluorosilicon copolymers, dehydrated sorbitol liquid crystals, soybean lecithin and silicon dioxide nanoparticles, we have constructed a defoamer with a multi-level rough structure. Cellulose nanocrystals and graphene can form an interlaced three-dimensional porous network, which is similar to the micro-nano structure on the surface of lotus leaves, which is conducive to increasing the contact area and permeability between the defoamer and the foam. Fluorosilicon copolymers and liquid crystal molecules can form a hydrophobic coating on the surface of cellulose / graphene skeletons, reduce surface tension, and destroy the foam structure. Lecithin and silicon dioxide nanoparticles play an emulsifying and dispersing role, which can improve the stability and uniformity of the system. Summary of the invention
[0008] The present invention provides a defoamer for treating garbage leachate and a preparation method thereof. The defoamer comprises the following raw materials in percentage by mass: Cellulose nanocrystals, 0.5wt%-2.0wt%; Hydrophobically modified graphene, 0.2wt%-1.0wt%; Fluorosilicone copolymer, 5.0wt%-15.0wt%; Sorbitan liquid crystal, 1.0wt%-5.0wt%; Soy lecithin, 0.5wt%-2.0wt%; Silica nanoparticles, 0.1wt%-1.0wt%; Deionized water, balance.
[0009] Cellulose nanocrystals and hydrophobically modified graphene are used as skeleton materials to construct a porous network structure, provide hydrophobic sites, and increase the specific surface area. Cellulose nanocrystals can be prepared from cellulose materials such as cotton and wood pulp through acid hydrolysis and mechanical crushing, with a size of 50-500nm and an aspect ratio greater than 50. Hydrophobically modified graphene is prepared from graphite through oxidation, exfoliation, and surface grafting of hydrophobic groups such as octadecyltrimethoxysilane, with a sheet size of 500nm-5μm, a thickness of less than 10nm, and a water contact angle greater than 120°.
[0010] Fluorosilicone copolymer is a defoaming active substance that reduces surface tension and destroys foam structure. It can be synthesized by hydrosilylation reaction of fluorinated propylene polyether and hydrogenated polysiloxane in the presence of platinum catalyst, with a molecular weight of 5000-50000 and a fluorine content of 5%-50%.
[0011] Dehydrated sorbitol liquid crystal acts as a thickener and foam stabilizer to adjust the rheology and adhesion of the defoamer. It can be prepared by dehydrating sorbitol under acid catalysis, with a liquid crystal phase content greater than 95% and a particle size less than 10μm.
[0012] Soy lecithin is used as an emulsifier to improve the dispersibility and emulsification stability of defoamers. It is extracted from soybeans through leaching and purification processes, with a lecithin content of more than 60% and an HLB value between 2-8.
[0013] Silica nanoparticles are used as defoaming aids and dispersants to improve the fluidity and stability of defoamers. They can be prepared by hydrolysis and polycondensation of ethyl silicate, with a particle size of 10-100nm.
[0014] The preparation process of the defoamer of the present invention comprises the following steps: S1. Preparation of cellulose nanocrystals: Microcrystalline cellulose was hydrolyzed in concentrated sulfuric acid, and then centrifuged, dialyzed and ultrasonicated to obtain a cellulose nanocrystal suspension, and its concentration was adjusted to 1.0-2.0wt%; S2. Preparation of hydrophobically modified graphene: The graphene was reacted with octadecyltrimethoxysilane under anhydrous conditions to obtain hydrophobically modified graphene, which was then ultrasonically dispersed in anhydrous ethanol to prepare a 0.5-1.0wt% dispersion; S3. Synthesis of fluorosilicone copolymer: Under anhydrous and oxygen-free conditions, vinyl fluoride ether and hydrogen-containing silicone oil are subjected to hydrosilylation reaction in the presence of a platinum catalyst to obtain a fluorosilicone copolymer, and its concentration is adjusted to 10-20wt%; S4. Soybean lecithin and sorbitol are mixed in a mass ratio of 1:2, added to anhydrous ethanol, heated to 70-80° C., and stirred to form a uniform liquid crystal precursor solution; S5. Take an appropriate amount of silica nanoparticles and ultrasonically disperse them in deionized water to prepare a 0.5-1.0wt% dispersion solution for standby use; S6. The cellulose nanocrystal suspension obtained in step S1 and the silica dispersion obtained in step S5 are mixed and stirred evenly; S7. Slowly add the hydrophobic modified graphene dispersion prepared in step S2 to the mixed solution obtained in step S6 and stir for 30-60 minutes; S8. The liquid crystal precursor solution obtained in step S4 is slowly added dropwise to the mixed solution in step S7, and stirring is continued for 30-60 minutes; S9. Slowly adding the fluorosilicone copolymer synthesized in step S3 to the mixed solution obtained in step S8, and emulsifying at high speed (speed 8000-12000 rpm) for 15-30 minutes; S10. The emulsion was transferred to a rotary evaporator and distilled under reduced pressure at 50-60°C to remove ethanol to obtain a concentrated defoamer; S11. Slowly add deionized water to the concentrated solution obtained in step S10 to adjust the final concentration of the defoaming agent to 10-20wt% to obtain a defoaming agent.
[0015] The preparation method is simple to operate, has low equipment requirements, stable product quality, high yield, and is easy to scale up. The reaction conditions of each step are mild, environmentally friendly, and have few by-products. By optimizing the dosage of each component and the preparation process parameters, a defoamer with superior performance can be obtained. DETAILED DESCRIPTION
[0016] In order to further illustrate the technical solutions and advantages of the present invention, a detailed description is given below in conjunction with specific embodiments.
[0017] Example 1 Formula composition: cellulose nanocrystals 1.5wt%, hydrophobically modified graphene 0.8wt%, fluorosilicone copolymer 12wt% (fluorine content 3.5wt%), dehydrated sorbitol liquid crystal 3wt%, soy lecithin 1wt%, silica nanoparticles 0.5wt%, water 81.2wt%.
[0018] Preparation steps: Avicel was hydrolyzed in 64 wt % sulfuric acid at 50 °C for 2 h, centrifuged, dialyzed, and ultrasonicated to obtain a 1.5 wt % cellulose nanocrystal suspension; Graphene and octadecyltrimethoxysilane were reacted at 80°C for 5 h under anhydrous and oxygen-free conditions, and ultrasonically dispersed in anhydrous ethanol to prepare a 0.8 wt% hydrophobically modified graphene dispersion; Vinyl fluoride ether and hydrogenated silicone oil (molar ratio 1:1) were reacted at 65°C for 10 h under the catalysis of chloroplatinic acid to obtain a fluorosilicone copolymer with an adjusted concentration of 12 wt%; Soybean lecithin and sorbitol were mixed in a ratio of 1:2, anhydrous ethanol was added, and stirred at 75°C for 30 minutes to form a liquid crystal precursor solution; The silica nanoparticles were ultrasonically dispersed in water to prepare a 0.5 wt % dispersion; The cellulose nanocrystal suspension and the silica dispersion were mixed evenly, and the hydrophobically modified graphene dispersion was added and stirred for 45 minutes; The liquid crystal precursor solution was added dropwise to the above mixed solution, and the stirring was continued for 45 minutes; then the fluorosilicone copolymer emulsifier was added, and the mixture was emulsified at a high speed of 10000 rpm for 20 minutes; The ethanol was distilled off under reduced pressure at 55°C, and water was added to adjust the concentration to obtain the final defoaming agent.
[0019] Example 2 Formula composition: cellulose nanocrystals 1.0wt%, hydrophobically modified graphene 0.5wt%, fluorosilicone copolymer 8wt% (fluorine content 4wt%), dehydrated sorbitol liquid crystal 2.5wt%, soy lecithin 1wt%, silica nanoparticles 0.2wt%, water 86.8wt%.
[0020] Preparation steps: Microcrystalline cellulose was hydrolyzed in 60 wt % sulfuric acid at 45 °C for 2.5 h, centrifuged, dialyzed, and ultrasonicated to obtain a 1 wt % cellulose nanocrystal suspension; Graphene and octadecyltrimethoxysilane were reacted at 85°C for 6 hours under anhydrous and oxygen-free conditions, and ultrasonically dispersed in anhydrous ethanol to prepare a 0.5 wt% hydrophobically modified graphene dispersion; Vinyl fluoride ether and hydrogenated silicone oil (molar ratio 1:1.2) were reacted at 70°C for 12 h under the catalysis of chloroplatinic acid to obtain a fluorosilicone copolymer with an adjusted concentration of 8 wt%; Soybean lecithin and sorbitol were mixed at a ratio of 1:2.5, anhydrous ethanol was added, and stirred at 70°C for 25 minutes to form a liquid crystal precursor solution; The silica nanoparticles were ultrasonically dispersed in water to prepare a 0.2 wt % dispersion; The cellulose nanocrystal suspension and the silica dispersion were mixed evenly, and the hydrophobically modified graphene dispersion was added and stirred for 40 minutes; The liquid crystal precursor solution was added dropwise to the above mixture and the stirring was continued for 40 minutes; then the fluorosilicone copolymer emulsifier was added and the mixture was emulsified at 9000 rpm for 18 minutes; The ethanol was distilled off under reduced pressure at 58°C, and water was added to adjust the concentration to obtain the final defoaming agent.
[0021] Example 3 Formula composition: cellulose nanocrystals 0.8wt%, hydrophobically modified graphene 0.3wt%, fluorosilicone copolymer 6wt% (fluorine content 4.5wt%), dehydrated sorbitol liquid crystal 1.5wt%, soy lecithin 0.8wt%, silica nanoparticles 0.3wt%, water 90.3wt%.
[0022] Preparation steps: Microcrystalline cellulose was hydrolyzed in 55 wt % sulfuric acid at 40 °C for 3 h, and a 0.8 wt % cellulose nanocrystal suspension was obtained by centrifugation, dialysis, and ultrasonic treatment; Graphene and octadecyltrimethoxysilane were reacted at 90°C for 7h under anhydrous and oxygen-free conditions, and ultrasonically dispersed in anhydrous ethanol to prepare a 0.3wt% hydrophobically modified graphene dispersion; Vinyl fluoride ether and hydrogenated silicone oil (molar ratio 1:1.5) were reacted at 75°C for 14 h under the catalysis of chloroplatinic acid to obtain a fluorosilicone copolymer with an adjusted concentration of 6 wt%; Soybean lecithin and sorbitol were mixed in a ratio of 1:2, anhydrous ethanol was added, and stirred at 65°C for 20 minutes to form a liquid crystal precursor solution; The silica nanoparticles were ultrasonically dispersed in water to prepare a 0.3 wt % dispersion; The cellulose nanocrystal suspension and the silica dispersion were mixed evenly, and the hydrophobically modified graphene dispersion was added and stirred for 35 minutes; The liquid crystal precursor solution was added dropwise to the above mixture and the stirring was continued for 35 minutes; then the fluorosilicone copolymer emulsifier was added and the mixture was emulsified at 8000 rpm for 15 minutes; The ethanol was distilled off under reduced pressure at 60°C, and water was added to adjust the concentration to obtain the final defoaming agent.
[0023] Example 4 Formula composition: cellulose nanocrystals 1.2wt%, hydrophobically modified graphene 0.6wt%, fluorosilicone copolymer 10wt% (fluorine content 3wt%), dehydrated sorbitol liquid crystal 4wt%, soy lecithin 1.5wt%, silica nanoparticles 0.8wt%, water 81.9wt%.
[0024] Preparation steps: Avicel was hydrolyzed in 62 wt % sulfuric acid at 48 °C for 2.2 h, centrifuged, dialyzed, and sonicated to obtain a 1.2 wt % cellulose nanocrystal suspension; Graphene was reacted with octadecyltrimethoxysilane at 82°C for 5.5h under anhydrous and oxygen-free conditions, and ultrasonically dispersed in anhydrous ethanol to prepare a 0.6wt% hydrophobically modified graphene dispersion; Vinyl fluoride ether and hydrogenated silicone oil (molar ratio 1:0.8) were reacted at 62°C for 9 h under the catalysis of chloroplatinic acid to obtain a fluorosilicone copolymer with an adjusted concentration of 10 wt%; Soybean lecithin and sorbitol were mixed at a ratio of 1:1.5, anhydrous ethanol was added, and stirred at 78°C for 35 minutes to form a liquid crystal precursor solution; The silica nanoparticles were ultrasonically dispersed in water to prepare a 0.8 wt % dispersion; The cellulose nanocrystal suspension and the silica dispersion were mixed evenly, and the hydrophobically modified graphene dispersion was added and stirred for 50 minutes; The liquid crystal precursor solution was added dropwise to the above mixed solution, and the stirring was continued for 50 minutes; then the fluorosilicone copolymer emulsifier was added, and the mixture was emulsified at a high speed of 11000 rpm for 22 minutes; The ethanol was distilled off under reduced pressure at 52°C, and water was added to adjust the concentration to obtain the final defoaming agent.
[0025] Example 5 Formula composition: cellulose nanocrystals 1.8wt%, hydrophobically modified graphene 1wt%, fluorosilicone copolymer 15wt% (fluorine content 5wt%), dehydrated sorbitol liquid crystal 5wt%, soy lecithin 1.8wt%, silica nanoparticles 1wt%, water 74.4wt%.
[0026] Preparation steps: Avicel was hydrolyzed in 68 wt % sulfuric acid at 55 °C for 1.8 h, centrifuged, dialyzed, and sonicated to obtain a 1.8 wt % cellulose nanocrystal suspension; Graphene and octadecyltrimethoxysilane were reacted at 95°C for 8 h under anhydrous and oxygen-free conditions, and ultrasonically dispersed in anhydrous ethanol to prepare a 1 wt% hydrophobically modified graphene dispersion; Vinyl fluoride ether and hydrogenated silicone oil (molar ratio 1:1.8) were reacted at 80°C for 16 h under the catalysis of chloroplatinic acid to obtain a fluorosilicone copolymer with an adjusted concentration of 15 wt%; Soybean lecithin and sorbitol were mixed at a ratio of 1:1.8, anhydrous ethanol was added, and stirred at 80°C for 40 minutes to form a liquid crystal precursor solution; The silica nanoparticles were ultrasonically dispersed in water to prepare a 1 wt % dispersion; The cellulose nanocrystal suspension and the silica dispersion were mixed evenly, and the hydrophobically modified graphene dispersion was added and stirred for 60 minutes; The liquid crystal precursor solution was added dropwise to the above mixture and the stirring was continued for 60 minutes; then the fluorosilicone copolymer emulsifier was added and the mixture was emulsified at 12000 rpm for 25 minutes; The ethanol was distilled off under reduced pressure at 62°C, and water was added to adjust the concentration to obtain the final defoaming agent.
[0027] We designed a set of comparative experiments and selected two common traditional defoamers on the market. Silicone defoamer: Dow Corning XIAMETER OFX-5211 defoamer, which is a highly efficient polydimethylsiloxane defoamer widely used in the fields of petroleum, chemical industry, wastewater treatment, etc. Polyether defoamer: BASF Defoamer MDP-66 defoamer, which is a composite defoamer based on polypropylene glycol and fatty alcohol polyoxyethylene ether. The defoaming time and antifoaming time of the landfill leachate were tested under the same conditions and compared with the five embodiments of the present invention.
[0028] The experimental steps are as follows: A leachate sample from a city landfill was selected, and its main properties were as follows: pH 8.2, COD 35000mg / L, ammonia nitrogen 2200mg / L, total nitrogen 3800mg / L, and total phosphorus 120mg / L.
[0029] 100 ppm of Dow Corning XIAMETER OFX-5211 defoamer, BASF Defoamer MDP-66 defoamer and aqueous solutions of Examples 1 to 5 of the present invention were prepared for use.
[0030] Take 1L of leachate sample and place it in a 2L defoaming test device, set the stirring speed to 120rpm, the aeration volume to 100mL / min, and the temperature to 25±1℃.
[0031] Add 5 mL of a specific defoamer solution (equivalent to 0.5% of the volume of the leachate), start the timer at the same time, and record the time t1 (defoaming time) required for the foam to completely disappear.
[0032] After the foam disappears, continue stirring and aerating, and record the time t2 (foam suppression time) required for the foam volume to recover to 50% of the original volume.
[0033] Repeat steps 3-5 three times for each defoamer and take the average value as the final result.
[0034] The experimental results are as follows:
[0035] As can be seen from the above table, compared with Dow Corning XIAMETER OFX-5211 silicone defoamer and BASF Defoamer MDP-66 polyether defoamer, the defoamer of the present invention shows obvious advantages in defoaming time and anti-foaming time. Taking Example 5 as an example, its defoaming time is shortened by about 4.7 times compared with XIAMETER OFX-5211 and about 6.5 times compared with BASF Defoamer MDP-66; while the anti-foaming time is increased by about 2.4 times and 3.3 times, respectively.
[0036] The experimental results further confirm the excellent performance of the defoaming agent provided by the present invention in defoaming time and anti-foaming time, which is attributed to the reasonable compounding and synergistic effect of various functional components. The porous network structure formed by cellulose nanocrystals and graphene increases the specific surface area of the defoaming agent, improves the contact area with the foam and the permeability; the fluorosilicone copolymer reduces the surface tension and destroys the foam structure; liquid crystal, lecithin, silicon dioxide, etc. play the role of thickening, emulsification, dispersion and stabilization.
Claims
1. A defoamer for treating landfill leachate, characterized in that: The defoamer comprises the following components in percentage by mass: Cellulose nanocrystals, 0.5wt%-2.0wt%; Hydrophobically modified graphene, 0.2wt%-1.0wt%; Fluorosilicone copolymer, 5.0wt%-15.0wt%; Sorbitan liquid crystal, 1.0wt%-5.0wt%; Soy lecithin, 0.5wt%-2.0wt%; Silica nanoparticles, 0.1wt%-1.0wt%; Deionized water, balance.
2. The defoamer according to claim 1, characterized in that The preparation method of the defoamer comprises the following steps: S1. Preparation of cellulose nanocrystals: Microcrystalline cellulose was hydrolyzed in concentrated sulfuric acid, and then centrifuged, dialyzed and ultrasonicated to obtain a cellulose nanocrystal suspension, and its concentration was adjusted to 1.0-2.0wt%; S2. Preparation of hydrophobically modified graphene: The graphene was reacted with octadecyltrimethoxysilane under anhydrous conditions to obtain hydrophobically modified graphene, which was then ultrasonically dispersed in anhydrous ethanol to prepare a 0.5-1.0wt% dispersion; S3. Synthesis of fluorosilicone copolymer: Under anhydrous and oxygen-free conditions, vinyl fluoride ether and hydrogen-containing silicone oil are subjected to hydrosilylation reaction in the presence of a platinum catalyst to obtain a fluorosilicone copolymer, and its concentration is adjusted to 10-20wt%; S4. Soybean lecithin and sorbitol are mixed in a mass ratio of 1:2, added to anhydrous ethanol, heated to 70-80° C., and stirred to form a uniform liquid crystal precursor solution; S5. Take an appropriate amount of silica nanoparticles and ultrasonically disperse them in deionized water to prepare a 0.5-1.0wt% dispersion solution for standby use; S6. The cellulose nanocrystal suspension obtained in step S1 and the silica dispersion obtained in step S5 are mixed and stirred evenly; S7. Slowly add the hydrophobic modified graphene dispersion prepared in step S2 to the mixed solution obtained in step S6, and stir for 30-60 minutes; S8. The liquid crystal precursor solution obtained in step S4 is slowly added dropwise to the mixed solution in step S7, and stirring is continued for 30-60 minutes; S9. The fluorosilicone copolymer synthesized in step S3 is slowly added to the mixed solution obtained in step S8, and high-speed shear emulsification is performed for 15-30 minutes; S10. The emulsion is transferred to a rotary evaporator and distilled under reduced pressure at 50-60° C. to remove ethanol to obtain a concentrated defoamer; S11. Slowly add deionized water to the concentrated solution obtained in step S10 to adjust the final concentration of the defoaming agent to 10-20wt%.
Citation Information
Patent Citations
Lotus leaf surface-imitated super-hydrophobic film and preparation method thereof
CN102093697A
Organic fluorosilicon modified epoxy anticorrosion coating and organic fluorine modified epoxy anticorrosion coating
CN108129890A
Defoaming agent used for wastewater treatment and preparation method thereof
CN108654148A
Novel environment-friendly composite defoaming agent for oil-water separation and preparation method thereof
CN108671589A
